PROCEDURAL CHALLENGES IN THE REGULATION OF ABUSE OF DOMINANT POSITION IN UZBEKISTAN - Sunnatillaeva, Sarvinoz (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article examines the evolution of competition policy in Uzbekistan, focusing on institutional reforms and regulatory challenges. It outlines the country's three-stage approach to developing competition laws and highlights recent efforts to strengthen the independence of the competition authority. Drawing comparisons with the European Union, the paper identifies areas for improvement, such as enhancing transparency and adopting economic tools for assessing abuse. By addressing these challenges, Uzbekistan can create a more competitive market environment conducive to economic growth.